Syrian Refugees' Education in Lebanon: Policies, Challenges, and Pathways Forward - Mousharafieh, Jacqueline (Université d'Ottawa | University of Ottawa, 2026)
This study critically examines Lebanon’s response to the Syrian refugee crisis through an analysis of the Reaching All Children with Education (RACE) I and II policy frameworks. Grounded in a Foucauldian understanding of power, knowledge, and discourse, and drawing on Fairclough’s three-dimensional model for critical discourse analysis, it analyzes policy texts to explore how RACE I and II construct the subject positions of Syrian refugee learners and how social inequalities are addressed or reproduced. The findings identify five key discursive mechanisms: the erasure of refugees’ agency, governance through technocratic rationalities, the relocation of responsibility, the normalization of temporariness and crisis, and the depoliticization of inequality. Together, these mechanisms reveal a form of humanitarian–technocratic governance in which authority is exercised indirectly and rendered non-political. The study contributes to the literature by unpacking the role of language in organizing power and responsibility within refugee education policy in Lebanon.
Keywords: Refugees; Education; Syrians; Critical Discourse Analysis; Lebanon